PENERAPAN MODEL BEYOND CENTERS AND CIRCLE TIME (BCCT) UNTUK MENINGKATKAN IDENTITAS KEBANGSAAN DI TAMAN KANAK-KANAK - Deni, Eka; Fadillah, Fadillah; Lukmanulhakim, Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study was intended to determine the impact of the application of Beyond Centers and Circle Time (BCCT) on understanding the national identity of children aged 5-6 years. Classroom Action Research (CAR) with two cycles of activities was used in this research. The observation sheet and discussion with the observer (partner teacher) were the method used in collecting data in this study, while the data analysis were carried out descriptively. The results showed that Beyond Centers and Circle Time (BCCT) turned out to increase the understanding of children aged 5-6 years of national identity. The results of the study also show that to implement Beyond Center and Circle Time (BCCT), the creativity of teachers is needed to organize the playing centers. The results of this study recommend that kindergarten teachers continue to be creative in organizing existing centers. In addition, this study also recommend that other researchers can make the results of this study for basis for conducting further research.       Key words: Beyond Centers and Circle Time (BCCT); national identitity